Nurses’ professional values and attitudes toward collaboration with physicians - Brown, Sara S (Nursing ethics, 2015)
Background:Growing evidence suggests that collaborative practice improves healthcare outcomes, but the precursors to collaborative behavior between nurses and physicians have not been fully explored.Research question:The purpose of this descriptive correlational study was to describe the professional values held by nurses and their attitudes toward physician–nurse collaboration and to explore the relationships between nurses’ characteristics (e.g. education, type of work) and professional values and their attitudes toward nurse–physician collaboration.Research design:This descriptive correlational study examines the relationship between nurses’ professional values (Nurses Professional Values Scale–Revised) and their attitudes toward nurse–physician collaboration (Jefferson Scale of Attitudes toward Physician–Nurse Collaboration).Ethical considerations:Permission to conduct the study was received from the hospital, and the Institutional Review Boards of the healthcare system and the participating university.Participants/context:A convenience sample of 231 registered nurses from a tertiary hospital in the United States was surveyed.Findings:A significant positive relationship was found between nurses’ professional values and better attitudes toward collaboration with physicians (r = .26, p < .01). Attitude toward collaboration with physicians was also positively associated with master’s or higher levels of education (F(3, 224) = 4.379, p = .005).Discussion:The results of this study can be helpful to nurse administrators who are responsible for developing highly collaborative healthcare teams and for nurse educators who are focused on developing professional values in future nurses.